Next generation maternal health: external shocks and health-system innovations. Issue 10057 (5th November 2016) - Kruk, Margaret E; Kujawski, Stephanie; Moyer, Cheryl A; Adanu, Richard M; Afsana, Kaosar; Cohen, Jessica; Glassman, Amanda; Labrique, Alain; Reddy, K Srinath; Yamey, Gavin
Summary: In this Series we document the substantial progress in the reduction of maternal mortality and discuss the current state of science in reducing maternal mortality. However, maternal health is also powerfully influenced by the structures and resources of societies, communities, and health systems. We discuss the shocks from outside of the field of maternal health that will influence maternal survival including economic growth in low-income and middle-income countries, urbanisation, and health crises due to disease outbreaks, extreme weather, and conflict. Policy and technological innovations, such as universal health coverage, behavioural economics, mobile health, and the data revolution, are changing health systems and ushering in new approaches to affect the health of mothers. Research and policy will need to reflect the changing maternal health landscape.